Public Governance: A Multidimensional Theoretical Approach To Raising Awareness of the Concept in the Arab Context - Al-Hajj, Abdulmalek Taher (The Arab Journal of Administration, 2025)
Governance has become one of the most widespread concepts in recent decades and has attracted the attention of academics, managers, politicians, and economists worldwide. Given the importance of this concept in research and practice, this study aimed to explore the nature of public governance (public sector governance) as a contemporary topic that is still ambiguous in the Arab world, as well as to investigate its intellectual and philosophical roots, the theories that attempt to explain it, also discussing its principles, and how it differs from private sector governance, besides analyzing the criticisms directed to public governance from a conceptual and applied perspective. An extensive literature review in this field was conducted based on the descriptive analytical approach. It resulted in a set of conclusions: Public governance is not a new idea but an old and renewed one. It has multiple origins and roots that appear directly and indirectly in ancient intellectual and philosophical works, supported by a set of new theories. Researchers and international institutions have proposed several overlapping models and principles for the practical application of the concept of governance. Also, it differs from private sector governance in many aspects: name, scope, objectives, accountability methods, stakeholders, and legal reference. In addition, researchers and practitioners have subjected governance to strict evaluation and criticism in its theoretical and practical dimensions. Finally, the study presented recommendations to improve public sector organizations’ governance in the Arab context.